First trigonotarbid arachnids from the Pennsylvanian of Indiana and Oklahoma. (July 2022) - Shanks, Ryan E.; Selden, Paul A.
Abstract: A new specimen of the arachnid order Trigonotarbida is described from the Middle Pennsylvanian (lower Desmoinesian) Shelburn Formation of Indiana, which has previously yielded the remains of a phalangiotarbid. Two new trigonotarbid arachnid specimens are also described from the Middle Pennsylvanian (Desmoinesian) Senora Formation of Oklahoma. These are the first trigonotarbid specimens reported from Indiana and Oklahoma. The Indiana trigonotarbid belongs to the Eophrynidae, as indicated by distinct features such as the large tubercles on the dorsal surface of the opisthosoma and two pairs of terminal opisthosomal spines. This specimen is the first arachnid fossil to be imaged using a Multistripe Laser Triangulation scanner. The heavy dorsal tuberculation, lobed and subtriangular carapace, rounded clypeus, lack of terminal opisthosomal spines, and rounded opisthosoma on Oklahoma specimen FMNH PE 56932 indicate it belongs to the genus Aphantomartus, in Aphantomartidae. The other Oklahoma specimen, FMNH PE 56955, possesses opisthosomal tergites that are divided into five plates longitudinally as well as a subquadrate carapace, which identify it as a member of Anthracomartidae; its rounded opisthosomal margin shows it to belong to the genus Anthracomartus .